2017
DOI: 10.1161/jaha.117.006896
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Duct Nitric Oxide Synthase 1ß Activation Maintains Sodium Homeostasis During High Sodium Intake Through Suppression of Aldosterone and Renal Angiotensin II Pathways

Abstract: BackgroundDuring high sodium intake, the renin‐angiotensin‐aldosterone system is downregulated and nitric oxide signaling is upregulated in order to remain in sodium balance. Recently, we showed that collecting duct nitric oxide synthase 1β is critical for fluid‐electrolyte balance and subsequently blood pressure regulation during high sodium feeding. The current study tested the hypothesis that high sodium activation of the collecting duct nitric oxide synthase 1β pathway is critical for maintaining sodium ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
3
23
1
Order By: Relevance
“…It is likely that reduced local NO in the renal inner medulla further contributes to the upregulation of renin production by the principal cells of the CD, and ultimately intrarenal Ang II content. In collecting duct nitric oxide synthase 1β knockout (CDNOS1KO) mice under changes in dietary salt, CD renin does not change in renal medullary tissues (Hyndman et al, 2017). However, in CD-eNOS-deficient mice used in the present study, renin immunostaining in cortical and medullary renal CD cells was augmented but not in JG cells.…”
Section: Discussioncontrasting
confidence: 51%
“…It is likely that reduced local NO in the renal inner medulla further contributes to the upregulation of renin production by the principal cells of the CD, and ultimately intrarenal Ang II content. In collecting duct nitric oxide synthase 1β knockout (CDNOS1KO) mice under changes in dietary salt, CD renin does not change in renal medullary tissues (Hyndman et al, 2017). However, in CD-eNOS-deficient mice used in the present study, renin immunostaining in cortical and medullary renal CD cells was augmented but not in JG cells.…”
Section: Discussioncontrasting
confidence: 51%
“…However, it was also shown that NO could inhibit sodium reabsorption in isolated collecting duct preparations of rats [ 48 ]. These data were confirmed in vivo in mice lacking nNOS in the collecting duct which exhibited significantly higher sodium retention when kept on a high-salt diet compared to WT-mice [ 49 ]. These natriuretic effects of NO might be mediated also by other NO-synthases and also be sex-specific since it is only in female that collecting duct specific eNOS knockout mice, that the sodium and water secretion was impaired [ 50 ].…”
Section: Impact Of the Impaired No/sgc/cgmp Signaling On Kidney Fumentioning
confidence: 77%
“…For controls 1/20 males and 3/18 females had mild damage with 2 or fewer protein casts detected. At 13 ± 4 weeks of age, mice were fed a low-sodium diet (<0.01% NaCl) followed by a week of HSD (4.0% NaCl) following our previously published protocols ( 23 , 24 ). Urine flow was significantly higher in male i Hoxb7 Hdac1/2KO mice compared with littermate controls on all salt diets ( Figure 3B , Supplemental Table 7 ), but sodium excretion was similar between the genotypes ( Supplemental Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mice were provided gel diets with different amounts of NaCl as described in detail elsewhere ( 24 ) for both the metabolic cage and telemetry studies. Mice were individually housed in the metabolic cages as previously described ( 24 ). Following the metabolic cage study, mice underwent telemetry surgery as previously described ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation